Knowledge management practices among workers in Yayasan Sarawak, Kuching / Ida Royanee Rosli - Rosli, Ida Royanee (2009)
This is a research of a case study of knowledge management practices among workers in Yayasan Sarawak, Kuching. The main objectives of this case study is to determine the level of knowledge management practices in the organization, to examine the influence of gender on perception towards Knowledge Management practices, to determine the effectiveness of Knowledge Management practices, to identify the barriers in practicing Knowledge Management and also to determine the relationship between Knowledge Management and overall organization effectiveness. For this case study, a random sample of 100 respondents was been distributed in a questionnaire method. After doing the test, the finding for the level of knowledge management practices in the organization is high. Moreover, the staffs in Yayasan Sarawak effectively implement knowledge management in their organization. Most of the respondents agree that one of the barriers in practicing knowledge management is lack of time or resources to concretely share knowledge on day-to-day basis. It is also said that there is relationship between Knowledge Management and overall organization effectiveness. Moreover, they should and must practice knowledge management and make it as a tool for better improvement in their organizations. Furthermore, promising and dedicated workers in implementing knowledge sharing should also be rewarded.